Phototropins of the moss Physcomitrella patens function as blue-light receptors for phototropism in Arabidopsis - Kimura, Yuki (Plant Signal Behav, 2018)
Four phototropin genes (PHOTA1, PHOTA2, PHOTB1, PHOTB2) have been isolated in the moss Physcomitrella patens. These genes encode phototropins that mediate blue-light–induced chloroplast movement. However, the individual functions of these phototropins, including the function of mediating blue-light–induced phototropism, remain unclear. To elucidate the individual functions of P. patens phototropins, each of these phototropin genes was expressed in a phototropin-deficient mutant of Arabidopsis (phot1-5 phot2-1). In addition, fluorescence of GFP fused to these phototropins was examined to determine the subcellular localization of each phototropin. Our results demonstrate that all four P. patens phototropins mediate blue-light–induced phototropism and are associated with the plasma membrane in Arabidopsis. Abbreviations GFP: green fluorescent protein; Pp_phot: Physcomitrella patens phototropin